Sistem Pejadwalan Kuliah Meggunakan Metode Algoritma Genetika pada Program Magister Fakultas Ekonomi dan Bisnis - yusuf afandi; Wiji Setiyaningsih (Fakultas Sains & Teknologi Universitas Kanjuruhan Malang, 2019)
As per the increase in students of the Masters Program, they will also increase the number of hours / lecture schedule. Willingness and readiness for lecturers make it difficult to determine the appropriate lecture schedule. In addition, the difficulty of making the lecture schedule is because there is still no automated system that can specifically schedule lectures. Limitations of available classrooms allow clash of schedules between classes and the complexity of scheduling courses is also experienced when 1 (one) course can be managed by 3 (three) lecturers (lecturer team). This causes a large number of errors in the scheduling process which results in collisions and delays in scheduling so that the learning and teaching process will be hampered if the scheduling process is still manual. This is important for an implementation to help the scheduling process in order to optimize collisions or collision schedules in the lecture process that occurs in the faculty. The results showed 93% of respondents from the aspects of the system, user aspects, and interaction aspects of designing and implementing a lecture scheduling system using genetic algorithms stated that it was very helpful and easy to apply as a tool to assist the process of optimizing lecture scheduling to minimize schedule clashes in lectures in the Masters Program.